2017
DOI: 10.1038/s41598-017-07520-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a male-produced sex-aggregation pheromone for a highly invasive cerambycid beetle, Aromia bungii

Abstract: The longhorned beetle Aromia bungii (Coleoptera: Cerambycidae) is a major pest of stone fruit trees in the genus Prunus, including cherries, apricots, and peaches. Its native range includes China, Korea, Mongolia, and eastern Russia, but it has recently invaded and become established in several countries in Europe, and Japan, and it has been intercepted in shipments coming into North America and Australia. Here, we report the identification of its male-produced aggregation pheromone as the novel compound (E)-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 3 publications
0
28
0
1
Order By: Relevance
“…Simultaneously, an early and correct flight monitoring of RLB adults is necessary for determining the best strategy to improve its management. Recent research on the efficacy of the identified pheromones of RLB 31,33,34 has opened interesting monitoring and control scenarios (i.e., mass trapping) where outbreaks of the pests are Scientific RepoRtS | (2020) 10:7112 | https://doi.org/10.1038/s41598-020-63959-9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, an early and correct flight monitoring of RLB adults is necessary for determining the best strategy to improve its management. Recent research on the efficacy of the identified pheromones of RLB 31,33,34 has opened interesting monitoring and control scenarios (i.e., mass trapping) where outbreaks of the pests are Scientific RepoRtS | (2020) 10:7112 | https://doi.org/10.1038/s41598-020-63959-9…”
Section: Discussionmentioning
confidence: 99%
“…Male (n = 60) 28.4 ± 0.42 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) 17.4 ± 0.28 (9-22.5) 10.5 ± 0.15 (6)(7)(8)(9)(10)(11)(12)(13) [Longevity] Female (n = 60) 31.5 ± 0.46 19.9 ± 0.27 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) 11.3 ± 0.17 (8)(9)(10)(11)(12)(13)(14)(15) [Longevity] Female (n = 10)…”
Section: Sex [Test] Body Length Elytra Metatibiaunclassified
See 1 more Smart Citation
“…development of mature larvae and during pupation) the frass produced in the excavation of larval galleries may accumulate around the base of the trunk or on the crown giving therefore indication of an infestation. Detection of infested trees is possible by detection of frass, mainly at the base of the trunk (although some may be seen on the bark or near the crown in upper branches) (Xu et al, 2017, Zou et al, 2019. If infestation is suspected, it is recommended to remove the bark of the tree to reveal larval galleries and holes ( Figure 5).…”
Section: Visual Examinationmentioning
confidence: 99%
“…Although it is native to China, it has been also reported in South Korea, Vietnam, Russia and elsewhere (Gong et al 2013) and has recently invaded and established in Japan and several European countries, including Germany and Italy (Burmeister et al 2012 andGaronna et al 2013). It has also been intercepted in the UK, USA and Australia causing widespread national concern (Xu et al 2017 andFukaya et al 2017).…”
Section: Introductionmentioning
confidence: 99%